Muslim friendly tourism: the promising tourism segments for Malaysia - Ismail, Noralisa; Anuar, Jazira; Deraman, Fauziah; Zakaria, Zainuddin (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2021)
The Muslim population is expected to increase from 1.6 billion people (23% of the world’s population as of 2010) to 2.76 billion people in 2050 (Pew Research Centre 2015). With the huge economic, demographic and destination potential of Islamic tourism and halal travel market, many countries, both Muslim and nonMuslim, are gearing their efforts to fulfil the requirements of the Muslim travel market.